Design and testing of a frictionless mechanical inerter device using living-hinges. Issue 14 (September 2019) - John, E.D.A.; Wagg, D.J.
Abstract: In this paper a novel type of frictionless mechanical inerter device is presented, where instead of gears, motion of the flywheel is achieved using living-hinges . The design is a type of pivoted flywheel inerter inspired in part by the Dynamic Anti-resonant Vibration Isolator (DAVI) concept, which was first developed in the 1960s. Unlike the DAVI, it will be shown that the pivoted flywheel inerter has the advantage of producing balanced forces. Furthermore the use of living-hinges eliminates the need for gears or other frictional elements in the inerter mechanism. To demonstrate the utility of the new concept, a bench-top experiment was performed using a small-scale living-hinge inerter manufactured using polypropylene hinges. By estimating the experimental system parameters, the transmissibility results from the experiment could be compared to a mathematical model. These results showed that the living-hinge inerter provided an isolation effect of at least three orders of magnitude in terms of the maximum amplitude reduction from the uncontrolled system compared to that with the inerter added. Although friction was eliminated, the living-hinges did introduce additional damping, and this was found to correspond to an increase in the equivalent damping ratio for the uncontrolled system of 1.2%. It is shown that the living-hinge inerter developed in this paper fits all of the essential conditions required to be a practical inerter device. Furthermore, as it operates without mechanical friction, or fluid flow, it represents a new paradigm in experimental inerter technology.